A new cloudinid fossil assemblage from the terminal Ediacaran of Nevada, USA. (16th February 2020) - Selly, Tara; Schiffbauer, James D.; Jacquet, Sarah M.; Smith, Emily F.; Nelson, Lyle L.; Andreasen, Brock D.; Huntley, John Warren; Strange, Michael A.; O'Neil, Gretchen R.; Thater, Casey A.; Bykova, Natalia; Steiner, Michael; et al.
Abstract : Owing to their temporal position during the decline of the classic Ediacara biota and the appearance of the more recognizable metazoans of the Cambrian Period, the terminal Ediacaran (∼551–539 Ma) assemblages of tubular fossil forms hold potential to improve understanding of biotic turnover near the end of the Ediacaran Period. Cloudinid taxa, including the terminal Ediacaran index fossil Cloudina, are the most well studied of these Ediacaran tubular forms due to their global palaeogeographical distribution. Recent reports revealed ecosystems of tubicolous organisms from the Great Basin region, Nevada, USA, and assigned taxa to such genera as Conotubus, Gaojiashania and Wutubus, well known from contemporaneous Chinese deposits. Appreciating the role that these organisms may have played in the evolutionary history of metazoans and recognizing their potential global distribution, however, requires careful taxonomic study. Here, we detail pyritized fossils from the Deep Spring and Wood Canyon formations of Esmeralda and Nye counties, Nevada, USA, respectively. Our investigation focused on the most abundant tubular taxon from the Nevada sites, which was previously generically assigned to Conotubus . While outwardly similar in morphology to this Gaojiashan taxon, our investigation determines that those fossils previously figured as Conotubus are instead two distinct taxa. The first represents a new species of Saarina – Saarina hagadorni sp. nov. – a genus previously known only from the East European platform, and the second is established as a novel genus and species, Costatubus bibendi gen. et sp. nov. http://zoobank.org/urn:lsid:zoobank.org:pub:CC391194-FF96-4BDF-B9B2-E4361DA64A5B